La ceramica sovra-dipinta proveniente dalle terme a Sud del Pretorio di Gortina (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2010)
The study of the 533 over-painted byzantine pottery fragments coming from the excavation in the Thermae located South of Gortyn Pretorio lead to some interesting issues. This kind of ceramic is produced in the city of Gortyn during the VII and VIII century. The analysis of the fragments, and in particular their decoration, let recognize some well-known shapes and point out the numerical superiority of the close-shapes over the open-shapes of ceramic class. On the ground of  these comparisons, new shapes are displayed besides the well-known ones, and many accurate decorations are visible together with Christian symbols as well.
Keywords: Crete; Gortyn; over-painted byzantine pottery; decoration